The Case for Cooperative Networking - Padmanabhan, Venkat; Sripanidkulchai, K. (First International Workshop on Peer-to-Peer Systems (IPTPS), 2002)
In this paper, we make the case for Cooperative Networking (CoopNet) where end-hosts cooperate to improve network performance perceived by all. In CoopNet, cooperation among peers complements traditional client-server communication rather than replacing it. We focus on the Web flash crowd problem and argue that CoopNet offers an effective solution. We present an evaluation of the CoopNet approach using simulations driven by traffic traces gathered at the MSNBC website during the flash crowd that occurred on September 11, 2001.